Fibromyalgia in Health Care Worker During COVID-19 Outbreak in Saudi Arabia - Fahidah AlEnzi; Sara Alhamal; Maryam Alramadhan; Ahmed Altaroti; Intisar Siddiqui; Ghada Aljanobi (Frontiers Media S.A., 2021)
Background: In the face of the contemporary COVID-19 pandemic, health service providers have emerged as the most at-risk individuals who are likely to contract the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).Aim: To measure the prevalence of fibromyalgia (FM) during COVID outbreak among health workers in Saudi Arabia using FiRST and LFESSQ tool.Methods: The study employed a cross-sectional methodology to explore the prevalence of Fibromyalgia among health workers at different health care settings in Saudi Arabia. The assessment of the prevalence of fibromyalgia among health worker was determined by using the Fibromyalgia Rapid Screening Tool (FiRST) and London Fibromyalgia Epidemiological Study Screening Questionnaire (LFESSQ) questionnaires. Descriptive statistics were used to summarize the data.Results: The sample size included 992 participants. The prevalence of fibromyalgia using FiRST and LFESSQ was 12.6 and 19.8%, respectively. In this study, the prevalence of fibromyalgia was higher in females when compared to males. Most of the respondents have Vitamin D deficiency. The relationship of fibromyalgia was significantly associated with the participants who worked during an outbreak, who covered COVID-19 inpatient, covered in-hospital on call and in area quarantine.Conclusion: The study's findings demonstrate that the prevalence of Fibromyalgia among health service providers during the current COVID-19 pandemic is considerably higher and that there are potential interventions that may be employed to mitigate the prevalence of the infection during the COVID-19 crisis.